Gefitinib versus placebo in completely resected non-small-cell lung cancer: results of the NCIC CTG BR19 study - Goss, Glenwood D; O'Callaghan, Chris; Lorimer, Ian; Tsao, Ming-Sound; Masters, Gregory A; Jett, James; Edelman, Martin J; Lilenbaum, Rogerio; Choy, Hak; Khuri, Fadlo; Pisters, Katherine; Gandara, David; et al. (Journal of clinical oncology, 2013)
Survival of patients with completely resected non-small-cell lung cancer (NSCLC) is unsatisfactory, and in 2002, the benefit of adjuvant chemotherapy was not established. This phase III study assessed the impact of postoperative adjuvant gefitinib on overall survival (OS). Patients with completely resected (stage IB, II, or IIIA) NSCLC stratified by stage, histology, sex, postoperative radiotherapy, and chemotherapy were randomly assigned (1:1) to receive gefitinib 250 mg per day or placebo for 2 years. Study end points were OS, disease-free survival (DFS), and toxicity. As a result of early closure, 503 of 1,242 planned patients were randomly assigned (251 to gefitinib and 252 to placebo). Baseline factors were balanced between the arms. With a median of 4.7 years of follow-up (range, 0.1 to 6.3 years), there was no difference in OS (hazard ratio [HR], 1.24; 95% CI, 0.94 to 1.64; P = .14) or DFS (HR, 1.22; 95% CI, 0.93 to 1.61; P = .15) between the arms. Exploratory analyses demonstrated no DFS (HR, 1.28; 95% CI, 0.92 to 1.76; P = .14) or OS benefit (HR, 1.24; 95% CI, 0.90 to 1.71; P = .18) from gefitinib for 344 patients with epidermal growth factor receptor (EGFR) wild-type tumors. Similarly, there was no DFS (HR, 1.84; 95% CI, 0.44 to 7.73; P = .395) or OS benefit (HR, 3.16; 95% CI, 0.61 to 16.45; P = .15) from gefitinib for the 15 patients with EGFR mutation-positive tumors. Adverse events were those expected with an EGFR inhibitor. Serious adverse events occurred in ≤ 5% of patients, except infection, fatigue, and pain. One patient in each arm had fatal pneumonitis. Although the trial closed prematurely and definitive statements regarding the efficacy of adjuvant gefitinib cannot be made, these results indicate that it is unlikely to be of benefit.